Segmentation of Tourist Using Demographic and Travel Characteristics: The Case of Istanbul - Birdir, Sevda Sahilli (International Review of Management and Marketing, 2015)
The purpose of this study is to analyze and segment tourists who visit Istanbul and to identify tourist profiles based of those demographic and travel characteristic. The questionnaire, in four languages (German, English, Russian and Turkish) was applied by the researcher to departing tourists between 13-18 January, 2015 at Istanbul International Airport using face to face technic. A total of 508 usable questionnaires were collected and analyzed applying arithmetic mean, t-test, crosstabulation, ANOVA, factor analysis, k-means cluster and multiple correspondence analysis. Factor analysis revealed six different factors among tourists visiting Istanbul. “Destination security” have been identified as the most important factor affecting tourists visiting Istanbul. Then, K-Means Cluster method was applied and produced three meaningful market segments. The clusters are named “natural beauty and information seekers”, “price sensitives” and “independents”. Finally, Multiple Correspondence Analysis was applied to identify statistical relationship among these clusters. Keywords: Segmentation; Factor Analysis; K-Means Cluster Analysis; Multiple Correspondence Analysis; Tourist profile JEL Classifications: L83